Characteristics and formation mechanism of karst collapse in Yunnan Plateau - Xiaobo KANG; Yu WANG; Hua ZHANG; Xusheng DAI; Guangyi ZHU (Zhongguo dizhi zaihai yu fangzhi xuebao, 2022)
The general characteristics of karst collapse in Yunnan plateau is comprehensively influenced and determined by the specific geological environment, karst development, hydrogeology, hydrometeorology and human engineering activities. This article analyses these factors and its mechanism, deepen the understanding on the basic characteristics and development law of karst collapse. The karst collapse in Yunnan Plateau is sporadically distributed, showing "point" characteristics, and mainly develops in karst geological environment units such as karst faulted basin, karst trough valley (depression) land, karst platform or ancient plateau surface.The main reason is that most of the plateau is exposed bedrock mountainous area, with deep rivers, vertical karst zones and deep groundwater.In basin, valley, depression and other areas inhabited by human beings, the overburden of loose soil is thicker, the proportion of cohesive soil layer is higher, and the degree of soil consolidation is higher, except for the marginal zone.Karst development is not uniform, karst caves and tubes are developed, but the underground karst rate is not high in general, and the caves and tubes that cause karst collapse are isolated and scattered.